Comparative experimental and EXAFS studies in the mizoroki-heck reaction with heteroatom-functionalised N-heterocyclic carbene palladium catalysts - Fiddy, Steven G.; Evans, John; Neisius, Thomas; Newton, Mark A.; Tsoureas, Nikolaos; Tulloch, Arran A.D.; Danopoulos, Andreas A. (Chemistry - A European Journal, 2007)
A study on the Mizoroki-Heck coupling of selected aryl bromides with acrylates catalysed by a series of Pd complexes of bidentate pyridyl-, picolyl-, diphenylphosphinoethyl- and diphenylphosphinomethyl-functionalised N-heterocyclic carbene (NHC) is reported. The observed activity is dependent on the type of solvent and base used and the nature of the "classical" donors of the mixed-donor bidentate ligand and its bite angle. A mechanistic model is presented for the pyridine-functionalised NHC complexes based on an in situ EXAFS study under dilute catalyst conditions (2 mM Pd). The model involves pre-dissociation of the pyridine functionality and oxidative addition of ArBr in the early stages of the reaction, as well as formation of monomeric and dimeric Pd species at the time of substrate conversion. © 2007 Wiley-VCH Verlag GmbH & Co. KGaA.
Keywords: Carbene ligands; EXAFS spectroscopy; Heck reaction; homogeneous catalysis; Palladium